Wsparcie podejścia procesowego przez systemy informatyczne z zastosowaniem koncepcji SOA - Wieczorkowski, Jędrzej; Polak, Przemysław (Supporting the Process Approach by Information Systems Using the Concept of SOA, 2009)
Service oriented architecture (SOA) is currently the most important concept used in the integration of information systems. It is strictly based on the process-oriented approach. The article presents the idea of SOA and its importance in relation to the business process approach to managing organizations. The authors indicate that SOA will remain a major method of systems integration, since it complements both with contemporary trends in management and the evolution of information technology.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 264-269